Targeting the invisible: precision fiducial marker placement in poorly visible liver tumors prior to percutaneous ablation using real-time image fusion guidance - Villard, N.; Tsoumakidou, G.; Gay, F.; Rousset, P.; Passot, G.; Muller, A.; Dumortier, J.; Valette, P. J.; Milot, L. (Frontiers in Radiology, 2025)
PurposeThis study aimed to assess the feasibility and accuracy of fiducial marker placement using US-CT/MRI fusion imaging guidance in poorly conspicuous liver tumors prior to percutaneous thermal ablation (PTA).MethodFrom January 2016 to February 2018, 30 consecutive patients with 38 liver lesions that were poorly or not visible on conventional ultrasound underwent fiducial marker placement under real-time US-CT/MRI fusion imaging before the PTA procedure. Marker position was confirmed via CT or MRI immediately after placement. The shortest distance between the marker and the edge of the target lesion, the lesion size, and the depth were measured. The fiducial marker placement was considered successful if the marker was within, in contact or ≤5 mm distance from the lesion; a distance >5 mm was considered a failure.ResultsOf the 38 lesions, 28 (74%) were undetectable using ultrasound alone, while 10 (26%) were not confidently identified. After fusion, 26 lesions (68%) showed enhanced visibility, while 12 (32%) remained undetectable. Overall, the mean distance between the fiducial marker and the lesion's edge was 4 mm (range: 0–45 mm). Successful placement was achieved in 30 lesions (79%): 27, inside or in contact, and 3, at a <5 mm distance from the target lesion. Placement was unsuccessful in eight lesions (21%). No procedure-related complications occurred.ConclusionsThe present work suggests that pre-PTA placement of a fiducial marker in poorly visible tumors using real-time US-CT/MRI fusion imaging is accurate, potentially enhancing the effectiveness of subsequent PTA.